Prevalence and correlates of insufficient physical activity in school adolescents in Peru - Sharma, Bimala (2018)
OBJECTIVE: To assess the prevalence and correlates of insufficient physical activity in adolescents in Peru. METHODS: We used a self-administered questionnaire developed from Global school-based Student Health Survey to collect information from secondary school students in North Lima and Callao in 2015. We carried out Poisson regression with robust variance using generalized linear models to estimate the crude and adjusted prevalence ratios (APR) with 95% confidence intervals (95%CI) of insufficient physical activity for its correlates. RESULTS: We have found that 78% of the adolescents did not meet the global recommendation of the World Health Organization on physical activity in the last week before the survey. Female respondents (APR = 1.13, 95%CI 1.04–1.21), respondents who perceived themselves as overweight (APR = 1.10, 95%CI 1.03–1.18), and respondents who consumed insufficient vegetables and fruits [no vegetables (APR = 1.30, 95%CI 1.06–1.59), no fruits (APR = 1.15, 95%CI 1.00–1.31) as compared to those who consumed ≥ 2 servings every day in the last seven days] were more likely to report insufficient physical activity. Adolescents who worked after school (APR = 0.92, 95%CI 0.84–0.99), had physical education classes five times per week (APR = 0.94, 95%CI 0.88–0.99), and had parental supervision (APR = 0.92, 95%CI 0.87–0.98) were less likely to report insufficient physical activity. CONCLUSIONS: Sex, work after school, perceived body weight, physical education class, parental support, and healthy dietary behaviors were associated with insufficient physical activity. Attempts to improve physical activity should look for ways to enhance leisure-time physical activity, parental support, physical education classes, healthy dietary behaviors, and normal body weight maintenance in adolescents with integrated efforts from the family and school.